TiO2 Based Dye-Sensitized Solar Cell Prepare by Using Spray Pyrolysis Deposition (SPD) - Taib, Syafa Syahirah; Ahmad, Mohd Khairul; Nayan, Nafarizal; Mohamad, Fariza; Fong, Soon Chin; Ameruddin, Amira Saryati; Abu Bakar, Faridah (International Journal of Integrated Engineering, 2018)
Titanium dioxide (TiO2) thin films have been produced on the Fluorine-doped Tin Oxide (FTO) glass substrates by using the techniques of spray pyrolysis deposition and annealed at different of temperature. The film was annealed within 3 hours for each thin film. The different temperature that used for annealed is 300℃, 400℃, and 500℃. In this study is shown that, when the temperature is increased, the efficiency of the thin film also increases. On the surface, morphology and electrical properties of TiO2 DSSC thin film were examined by using FESEM and electrical measurement was calculated by I-V analysis. FESEM procedure characterizes, is for surface morphology and grain size. Raman spectroscopy analysis used to provide a fingerprint by which molecules can be identified and information about molecular vibrations that can be used for sample identification and quantitation. on electrical properties, the measurement of resistance and resistivity used common methods 2 point-prob and the efficiency of DSSC was measured by Solar Simulator. At the end, the objectives accomplish to produce TiO2 thin film with high efficiency to be applied in the DSSC.